THE PRESISPOSED INFLUENCE OF TALENT MANAGEMENT, KNOWLEDGE SHARING, SERVANT LEADERSHIP ON INNOVATIVE WORK BEHAVIOR - A Hadi Arifin; Rita Rahmi; Faisal Matriadi; Em Yusuf IiS (RADJA PUBLIKA, 2023)
This research investigates the influence of talent management, knowledge sharing, and servant leadership on innovative work behavior at Bank Syariah Indonesia Lhokseumawe Branch. Data was collected through questionnaires as a data collection instrument. The population in this study was 60 employees. Data analysis using a quantitative approach to multiple linear regression version of the Statistical Package for the Social Sciences. The research results show that talent management, knowledge sharing, and servant leadership significantly positively affect innovative work behavior. These findings provide practical implications for the management of Bank Syariah Indonesia to strengthen and optimize talent management strategies, knowledge sharing, and servant leadership. By paying more attention to this third variable, companies can create a work environment that supports and encourages innovation, improving the organization's performance and competitive advantage in an increasingly complex and dynamic market.